MAP symbol estimation on frequency-flat Rayleigh fading channels via a Bayesian EM algorithm. - Chiavaccini, E.
In this paper, an expectation-maximization (EM) technique for maximum a posteriori estimation is employed to devise novel soft-in soft-out algorithms for symbol detection over frequency-flat Rayleigh fading channels. An application of these algorithms to iterative decoding of coded PSK signals is proposed and some performance results are illustrated
Keywords: Bayesian EM algorithm; MAP symbol estimation; Coded PSK signals; Expectation-maximization technique; Frequency-flat Rayleigh fading channels; Iterative decoding; Maximum a posteriori estimation; Soft-in soft-out algorithms; Symbol detection